2023
DOI: 10.1038/s41419-023-05814-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel insight into the underlying dysregulation mechanisms of immune cell-to-cell communication by analyzing multitissue single-cell atlas of two COVID-19 patients

Abstract: How does SARS-CoV-2 cause lung microenvironment disturbance and inflammatory storm is still obscure. We here performed the single-cell transcriptome sequencing from lung, blood, and bone marrow of two dead COVID-19 patients and detected the cellular communication among them. Our results demonstrated that SARS-CoV-2 infection increase the frequency of cellular communication between alveolar type I cells (AT1) or alveolar type II cells (AT2) and myeloid cells triggering immune activation and inflammation microen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…FPR1 was found to induce blood neutrophil activation in COVID-19 patients, triggering neutrophil-mediated inflammation and end-organ damage [43]. It has also been found that T cells and myeloid cells from COVID-19 patients may trigger an inflammatory storm in the lungs through intercellular communication via the ANXA1/FPR1 receptor-ligand signaling pathway [44] The study by Lee H et al [45] also concluded that FPR1 is a suitable target for appropriate assessment of COVID-19 severity and provision of therapeutic agents. FCGR2A is a member of the family of genes encoding immunoglobulin Fc receptors present on the surface of many immuneresponsive cells.…”
Section: Discussionmentioning
confidence: 99%
“…FPR1 was found to induce blood neutrophil activation in COVID-19 patients, triggering neutrophil-mediated inflammation and end-organ damage [43]. It has also been found that T cells and myeloid cells from COVID-19 patients may trigger an inflammatory storm in the lungs through intercellular communication via the ANXA1/FPR1 receptor-ligand signaling pathway [44] The study by Lee H et al [45] also concluded that FPR1 is a suitable target for appropriate assessment of COVID-19 severity and provision of therapeutic agents. FCGR2A is a member of the family of genes encoding immunoglobulin Fc receptors present on the surface of many immuneresponsive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mucins belong to the first defense against pathogens in the airways and are essential for mucociliary correction; high expression of MUC5B may be related to worse prognosis of SARS-CoV-2 infection [ 8 , 14 , 17 ]. The rs35705950 SNP present in this gene is described as an important variant associated with hospitalization and idiopathic pulmonary fibrosis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…By exposing human HEK293T cells to the SARS-CoV-2 spike gene plasmid, the synthesis of spike glycoprotein is induced within the cell, which releases large amounts of EVs containing the spike glycoprotein along with specific miRNAs [89,95]. Furthermore, long-distance cell-to-cell communication mediated by EVs may be a mechanism by which neurological symptoms manifest in severe cases of COVID-19 [96,97]. Through inhibition of ubiquitin-specific peptidase 33 (USP33) and IRF9, two key proteins that control this pathway, two miRNAs, miR-148a and miR-590, specifically inhibit type I interferon signaling [98].…”
Section: Vaccination With Nanoparticles (Lnp) and Extracellular Vesic...mentioning
confidence: 99%